O (a) trabalhador (a) terceirizado (a) em uma universidade pública: percepções sobre organização do trabalho e educação em saúde - Silva, Ada Priscila da [UNIFESP] (2020)
Labor relations have become increasingly fragile due to the outsourcing policies adopted in Brazil since the 1990s and enhanced over the recent years. As to Federal Public Universities, there is a constant reduction of funds for their operation, which has created an environment of insecurity in outsourced workers. This research aims to understand the work of the outsourced at Unifesp- Campus Baixada Santista regarding work conditions, processes, organization and work relationships and the influences on the worker’s health. It aims to identify the needs of these workers in health education and verify their expectations about the studies developed within the University where they work. The research has a qualitative focus and is formed by non-exhaustive observation of each outsourced service on the Campus, combined with the Discourse of the Collective Subject, carried out through semi-structured individual interviews with the workers. The study points out that the health of outsourced employees is negatively affected by the precariousness resulting from the outsourcing policies and the constant decline of financial resources given to Public Universities. The research revealed that the downsizing of outsourced personnel and the fear of unemployment worry workers and are causes of health compromise according to studies in the area. In addition, bad structural conditions and work organization were also found. Eventually, the research showed that outsourced workers are unfamiliar with what is developed at the University. Based on the obtained results, we propose meetings with different groups of the campus in order to promote the exchange of knowledge about work and health, as well as to bring these groups together.